Fuelwood characteristics of ten fast-growth species in Costa Rica - Moya-Roque, Róger (2013)
The aim of this study was to investigate the fuelwood characteristics (calorific value and fuelwood value index) of ten species utilized in commercial reforestation in Costa Rica. It was evaluated too the chemical characteristics (cellulose, lignin, ash, carbon and nitrogen) and physical properties (moisture content, green density and specific gravity) on these species. The results showed that the maximum calorific value ranged from 16500 to 20594 kJ/kg for sapwood and from 16258 to 20119 kJ/kg for heartwood. It was not possible to establish if heartwood has best fuelwood characteristics in relation to sapwood. The fuelwood value index presented large variations, from 337 to 6390. The effect of moisture content on the calorific value was linear and can be modeled by Y= β0*X+ β1. This relationship varied for each species or type of wood (heartwood or sapwood). Just Cupressus lusitanica between 10 studied species, presented the greatest fuel potential due to its high fuelwood value index, calorific value and low ash content. Others reforestation species, although not exhibit same fuelwood values than C. lusitanica, they have a significant energy potential due to the high volumes of waste obtained from different industries.